Following Political Science Students Through Their Methods Training: Statistics Anxiety, Student Satisfaction, and Final Grades in the COVID Year 2021/22 - Paul Vierus; Jonas Elis; Achim Goerres; Conrad Ziller; Jan Karem Höhne (Politische Vierteljahresschrift, 2025)
Teaching empirical social research methods as a compulsory part of a curriculum involves several challenges. Students are often unaware of the relevance of methodological training for their political science education and its value as a transferable skill. In addition, some students are afraid of the mathematical components of their applied statistics training. These challenges can have a diminishing effect on student success. We examine three different perspectives of students' satisfaction with methods courses at a large political science department in a German university. We describe temporal changes in student satisfaction over the course of a complete term (6 months) and use a set of independent variables to explain the outcomes. To do this, we fielded a longitudinal survey in five in-person methods and statistics courses during 2021/2022 after the height of the COVID-19 pandemic in Germany. We demonstrate that statistics anxiety—the self-reported worries about getting lower grades, becoming nervous, or feeling helpless when solving tasks that focus on statistics—has a substantial negative effect both on student satisfaction and on their final grades. This clear pattern raises the question of how to optimally support students who exhibit high levels of negative emotions towards statistics. Our findings contribute to the understanding of course satisfaction in academic methodological training and can be used to improve the design of courses in order to significantly reduce failure and dropout rates.
Keywords: 320; Teaching; Longitudinal; Methodology; University; Germany; Student panel; Lehre; Längsschnitt; Methodik; Universität; Deutschland; Studierendenpanel